Water reticulation model for Taman Maju, Parit Raja - O. Elojali, Otman Mohamed (2011)
A numerical model is developed to quantify energy head losses occurred in the water distribution network of Taman Maju, Parit Raja, Johor. A numerical computation has the advantage over a manual computation when analyzing a complex distribution network. The programming language used in this study is the Microsoft Visual Basic 6.0. Hardy-Cross method is selected to calculate the total energy head loss incurred in the looped water distribution network of Taman Maju. The type of pipe used in the water distribution network of Taman Maju is the unplasticised polyvinyl chloride (uPVC) type with the roughness coefficient k = 0.0015 mm. Since Taman Maju consists of terrace houses, the water demand is 1360 litres/unit/day. Three loop networks are considered, namely loop A, B and C for Taman Maju reticulation system. The final flow rate in each pipe has been obtained. This model is helpful in reducing the period of time to calculate the flow rate which is found to be within the piping system design requirement. If comparison is made between the manual calculation, it will definitely shows some difference. The final result will be different because the decimal places fixed are different in manual and model